2014
DOI: 10.1159/000362901
|View full text |Cite
|
Sign up to set email alerts
|

Itching in Patients with Chronic Hand Eczema: Data from the CARPE Registry

Abstract: Background: Itching is a leading symptom of chronic hand eczema (CHE) having a great impact on patients. The determinants of itching in CHE are unclear. Objective: We performed a cross-sectional analysis investigating factors associated with the presence and severity of itch in CHE patients from the CARPE registry. Methods: We present baseline data on itch in relationship with sociodemographic factors, severity of CHE, atopy, contact allergy, treatment and patient- reported outcomes including health-related qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
(36 reference statements)
2
18
0
Order By: Relevance
“…Its negative consequences on the hand functions and the patient’s quality of life are all related to the symptomatology of the condition. Patients may suffer from pruritus, burning and stinging pain, 17 desquamation, vesiculation, erythema, fissuring, oozing or dryness in different combinations during the course of the disease 18 . Out of these symptoms, pruritus may be the most frequent and bothersome symptom to the patient 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its negative consequences on the hand functions and the patient’s quality of life are all related to the symptomatology of the condition. Patients may suffer from pruritus, burning and stinging pain, 17 desquamation, vesiculation, erythema, fissuring, oozing or dryness in different combinations during the course of the disease 18 . Out of these symptoms, pruritus may be the most frequent and bothersome symptom to the patient 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients may suffer from pruritus, burning and stinging pain, 17 desquamation, vesiculation, erythema, fissuring, oozing or dryness in different combinations during the course of the disease 18 . Out of these symptoms, pruritus may be the most frequent and bothersome symptom to the patient 17 . It may be an exacerbating factor for the other symptoms as consequent rubbing or scratching will further compound the skin barrier defect.…”
Section: Discussionmentioning
confidence: 99%
“…Itching as a symptom is unreliable in distinguishing between allergic and irritant causation in the chronic phase. A recent study of itching in chronic hand dermatitis unresponsive to topical therapy found an association of itching with atopy and disease severity among other factors [11].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…CARPE serves several clinical and scientific purposes. For instance, we previously analysed co‐factors of pruritus accompanying CHE and observed that younger age, a more severe CHE and moderate or severe impairment in health‐related quality of life were significantly associated with pruritus in CHE . A subsample of the CARPE baseline dataset was used to validate the German version of the Occupational Contact Dermatitis Disease Severity Index (ODDI) .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we previously analysed co-factors of pruritus accompanying CHE and observed that younger age, a more severe CHE and moderate or severe impairment in health-related quality of life were significantly associated with pruritus in CHE. 4 A subsample of the CARPE baseline dataset was used to validate the German version of the Occupational Contact Dermatitis Disease Severity Index (ODDI). 5 A comprehensive descriptive analysis of the care received by patients with CHE showed that 35.3% (N = 1163) reported systemic treatment prior to inclusion in the register, including e.g.…”
Section: Introductionmentioning
confidence: 99%